Socialization of Composting Technology for Culinary Waste Management in Kampung Emas - Kusmendar Kusmendar; Arya Dani Setyawan; Ardian Arief; Yudam Alkolid; Tri Aji Purnomo; Nurul Istiqomah; Refiana Eka Asita Damayanti; Rina Apriyanti (Indonesian Journal Publisher, 2023)
The Kampung Emas Tourism Area, renowned for its traditional eateries offering authentic Javanese cuisine, has become a favored destination for tourists. However, the surge in tourist numbers has contributed to increased organic waste. Addressing this issue is crucial to prevent environmental problems and negative perceptions of Kampung Emas. The community service initiative aims to introduce rapid composting technology as an innovative solution to enhance understanding and effectiveness in waste management within Kampung Emas. The activity was conducted on August 12, 2023, involving 15 managers from the tourism sector. Emphasizing organic waste management, the initiative introduced the innovative solution of rapid composting technology. Evaluation was carried out through questionnaires distributed before and after the activity. Participants grasped organic waste management concepts yet demonstrated a greater understanding of composting technology. The evaluation results showed a significant improvement post-activity, with an understanding rate of 83% for waste management concepts and 60% for composting technology. In conclusion, the initiative successfully increased knowledge and understanding among Kampung Emas management regarding rapid composting technology, providing a solid foundation for implementing more effective and sustainable culinary waste management practices.